Prospective study of dilated cardiomyopathy in dogs eating nontraditional or traditional diets and in dogs with subclinical cardiac abnormalities. (17th March 2022) - Freeman, Lisa; Rush, John; Adin, Darcy; Weeks, Kelsey; Antoon, Kristen; Brethel, Sara; Cunningham, Suzanne; Santos, Luis Dos; Girens, Renee; Goldberg, Robert; Karlin, Emily; Lessard, Darleen; et al.
Abstract: Background: Recent studies have investigated dogs with presumed diet‐associated dilated cardiomyopathy (daDCM), but prospective studies of multiple breeds are needed. Hypothesis/Objectives: To evaluate baseline features and serial changes in echocardiography and cardiac biomarkers in dogs with DCM eating nontraditional diets (NTDs) or traditional diets (TDs), and in dogs with subclinical cardiac abnormalities (SCA) eating NTD. Animals: Sixty dogs with DCM (NTD, n = 51; TDs, n = 9) and 16 dogs with SCA eating NTDs. Methods: Echocardiography, electrocardiography, and measurement of taurine, cardiac troponin I, and N‐terminal pro‐B‐type natriuretic peptide were performed in dogs with DCM or SCA. Diets were changed for all dogs, taurine was supplemented in most, and echocardiography and cardiac biomarkers were reassessed (3, 6, and 9 months). Results: At enrollment, there were few differences between dogs with DCM eating NTDs or TDs; none had low plasma or whole blood taurine concentrations. Improvement in fractional shortening over time was significantly associated with previous consumption of a NTD, even after adjustment for other variables ( P = .005). Median survival time for dogs with DCM was 611 days (range, 2‐940 days) for the NTD group and 161 days (range, 12‐669 days) for the TD group ( P = .21). Sudden death was the most common cause of death in both diet groups. Dogs with SCA also had significant echocardiographic improvements over time. Conclusions and Clinical Importance: Dogs with DCM or SCA previously eating NTDs had small, yet significant improvements in echocardiographic parameters after diet changes.